Letter to Jane Tolmach; from George Grimes - George Grimes:::::: (1963)
Letter to Jane Tolmach from George Grimes (Chairman, Board of Trustees) sent on April 11, 1963. George Grimes shares that the upcoming Board of Trustees meet at the Camarillo State Hospital on April 23rd, will be Dr.Garrett's last one. Dr. Garret the superintendent will be retiring and George Grimes is asking the support from trustees such as Jane Tolmach to create a resolution honoring Dr.Garrett's service as a thank you.